Study on the skidding performance of stone mastic asphalt - Amiruddin, Mohd. Noor Asyraf (2010)
Road accidents are a significant source of community costs associated with transport operations. More than a quarter of all wet-road accident in the Malaysia is related to skidding conditions, conditions which could be avoided if application of exact road technologies. Therefore, a study is done to know the skidding performance of Stone Mastic Asphalt (SMA) during rainfall. The main objective of this study is to measure skid performance of SMA under various conditions which is different rainfall intensity and different crossfall percentage. The test result is compared to the skidding performance of ACW from previous study. This study use rainfall simulator in order to simulate different rainfall intensity and different percentage of crossfall. The Portable Skid Tester was used during rainfall for measurement of skid performance. Sand Patch Method is applied on road surface for determining the texture depth of SMA 14. Results from this study shows that, at crossfall between 0% - 4%, the skid resistance for SMA14 is higher than ACW14. However at high crossfall between 6% - 10%, the skid resistance for ACW14 is higher than SMA14.